Does Extended Serum Sample Storage Impact Laboratory Results? - Balaji Pillai; Ajeet Kumar Khilnani; Dinesh Sharma (GAIMS Journal of Medical Sciences)
Background: Prolonged storage of samples can result in changes to routine biochemical parameters.